EDUKASI PENCEGAHAN BULLYING MELALUI PENGUATAN MOTIVASI MERAIH CITA-CITA PADA SISWA SEKOLAH DASAR - Wa Ode Husniah; Edison Edison; Erviana Antasari; Muhamad Aditsyan Kamil (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service activity on Bullying Prevention Education through strengthening achievement motivation was carried out as a preventive effort to reduce bullying behavior while fostering students’ enthusiasm for achieving their goals. The program was initiated in response to the continued prevalence of bullying cases in elementary schools, which negatively affect children’s social, emotional, and learning motivation development. The activity took place at SD Negeri 20 Buton and involved 30 fifth-grade students. A training approach with mixed techniques was used, including interactive lectures, group discussions, and role-playing activities. The results showed an improvement in students’ understanding of the dangers of bullying and increased awareness to behave positively in the school environment. Students also demonstrated strong enthusiasm in expressing their aspirations and understanding the connection between good attitudes, hard work, and future success. This program indicates that strengthening achievement motivation from an early age can be an effective strategy to prevent bullying and build empathetic and confident character in children